2023
DOI: 10.3390/medicina59040743
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Farnesol with Common Antifungal Drugs: Inhibitory Effect against Candida Species Isolated from Women with RVVC

Abstract: Background and Objectives: Vulvovaginal candidiasis (VVC) is a mucous membrane infection, with an increased rate of antifungal resistance of Candida species. In this study, the in vitro efficacy of farnesol alone or in combination with traditional antifungals was assessed against resistant Candida strains recovered from women with VVC. Materials and Methods: Eighty Candida isolates were identified by multiplex polymerase chain reaction (PCR), and the antifungal susceptibility to amphotericin B (AMB), fluconazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Moreover, some C. glabrata strains are characterized by intrinsic resistance to this antifungal agent [ 12 , 36 ]. Even though azoles are the drugs of first choice in treating candidiasis, pathogens’ susceptibility has decreased dramatically in the last few decades, according to the development of various resistance mechanisms [ 36 , 37 ]. Therefore, the current stock of drugs used to combat fungal infections remains inadequate, and infections caused by C. glabrata strains resistant to a single drug and multiple drugs are becoming a common and difficult therapeutic challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some C. glabrata strains are characterized by intrinsic resistance to this antifungal agent [ 12 , 36 ]. Even though azoles are the drugs of first choice in treating candidiasis, pathogens’ susceptibility has decreased dramatically in the last few decades, according to the development of various resistance mechanisms [ 36 , 37 ]. Therefore, the current stock of drugs used to combat fungal infections remains inadequate, and infections caused by C. glabrata strains resistant to a single drug and multiple drugs are becoming a common and difficult therapeutic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Searching for new efficient antifungal agents with minimal adverse effects and low toxicity often leads to abundant resources of natural substances, which are mainly present in plants [ 18 , 37 , 39 ] and bee products [ 40 ]. Compounds from natural products not only exhibit antifungal activity but also enhance the effects of synthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition is achieved by negatively regulating the RAS1-cAMP-PKA pathway by targeting CYR1. Farnesol has recently become a prospective drug due to its antifungal efficacy (Nikoomanesh et al, 2023). Probiotic vaginal colonization, particularly with Lactobacillus sp., has also been widely studied and shown to have a significantly lower risk of VVC and to even treat VVC.…”
Section: Existing Treatment Strategies For Vvcmentioning
confidence: 99%
“…For instance, Brasch et al (2014) detailed their effectiveness versus dermatophytes while Katragkou et al (2015) showed their synergistic effectiveness with fluconazole, amphotericin B, and micafungin versus C. albicans biofilms. More recently, Nagy et al (2020) reported that farnesol inhibited growth and biofilm forming ability by C. auris, Dekkerova et al (2022) confirmed a synergistic effect between farnesol and fluconazole in C. auris, and Nikoomanesh et al (2023) confirmed a synergism between farnesol and either fluconazole or itraconazole which restored the original sensitivity of azole-resistant C. albicans and Candida parapsilosis. The idea that C. albicans secretes antifungal molecules as a mechanism of competition with other fungi is longstanding.…”
Section: Introductionmentioning
confidence: 96%